Exacerbated salmonellosis in poly(ADP-ribose) polymerase 14-deficient mice - Vedantham, Madhukar; Polari, Lauri; Rissanen, Tiia; Pulliainen, Arto Tapio (American Society for Microbiology, 2026)
Salmonella enterica subspecies enterica serovar Typhimurium is an enteropathogen annually causing millions of acute infections ranging from gastroenteritis to life-threatening systemic disease. Strong mucosal inflammation, a process with incomplete molecular understanding, is characteristic of S. Typhimurium gastroenteritis. Here, we investigated functions of the nucleocytoplasmic protein poly(ADP-ribose) polymerase (Parp14) in the mouse model of S. Typhimurium infection. Using a systemic Parp14 knockout approach, we found that infected Parp14-deficient mice suffered from exacerbated histopathology, in particular, in the large intestine, that is, increased immune cell infiltration, goblet cell loss, and epithelial erosion. A bulk tissue and single-cell RNA-Seq analysis supplemented with TaqMan qPCR assays was executed to obtain molecular-level functional approximations. We found evidence of a defective Th17 response in the infected Parp14-deficient mice. This parallels the known cell-intrinsic regulatory function of Parp14 in Th17 cell differentiation. However, based on immunohistochemistry, we found that Parp14 was also expressed by macrophages and, in particular, by epithelial cells across the mucosal tissues in small intestine, cecum, and large intestine. The bulk tissue and epithelial cell subtype single-cell RNA-Seq data comparison revealed a plausible epithelial cell-specific transcriptomic signature defective in the infected Parp14-deficient mice. Downregulation of ApoA1, Spink1, and Sst, encoding apolipoprotein A1, serine protease inhibitor Kazal-type 1, and somatostatin, respectively, was characteristic of this defective transcriptomic signature. We conclude that Parp14 is an integral part of the physiological response to S. Typhimurium infection and that Parp14 acts as a multi-cell-type pleiotropic regulator of mucosal inflammation.